2017
DOI: 10.1111/1751-7915.12772
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of oxidative balance in the gut of the western honeybee Apis mellifera exposed to the intracellular parasite Nosema ceranae and to the insecticide fipronil

Abstract: SummaryThe causes underlying the increased mortality of honeybee colonies remain unclear and may involve multiple stressors acting together, including both pathogens and pesticides. Previous studies suggested that infection by the gut parasite Nosema ceranae combined with chronic exposure to sublethal doses of the insecticide fipronil generated an increase in oxidative stress in the midgut of honeybees. To explore the impact of these two stressors on oxidative balance, we experimentally infected bees with N. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 79 publications
(126 reference statements)
1
30
0
1
Order By: Relevance
“…Oncorhynchus mykiss infected by Streptococcus (Hoseinifar et al, 2017). In our study, the expression of genes encoding catalase and glutathione peroxidase involved in antioxidant reaction and xenobiotic detoxification was decreased in infected bees suggesting a disruption of the oxidative balance as previously reported by Aufauvre et al (Aufauvre et al, 2014) and Paris et al (Paris et al, 2017). The oxidative balance is essential for the honeybee health since reactive oxygen species (ROS) could be both beneficial (immune defence, signal transduction, cell cycle regulation) and dangerous (DNA, lipid or protein damages) for the honeybees (Chiu and Dawes, 2012;Finkel, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Oncorhynchus mykiss infected by Streptococcus (Hoseinifar et al, 2017). In our study, the expression of genes encoding catalase and glutathione peroxidase involved in antioxidant reaction and xenobiotic detoxification was decreased in infected bees suggesting a disruption of the oxidative balance as previously reported by Aufauvre et al (Aufauvre et al, 2014) and Paris et al (Paris et al, 2017). The oxidative balance is essential for the honeybee health since reactive oxygen species (ROS) could be both beneficial (immune defence, signal transduction, cell cycle regulation) and dangerous (DNA, lipid or protein damages) for the honeybees (Chiu and Dawes, 2012;Finkel, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Honeybees were collectively infected J o u r n a l P r e -p r o o f two days after the emergence with a dose of 10 000 N. ceranae spores per bee in the sucrose solution. At the end of the experiment (D22), abdomens of five honeybees per cage were dissected to evaluate the spore load according to Paris et al (Paris et al, 2017).…”
Section: Nosema Ceranae Infection Proceduresmentioning
confidence: 99%
“…The increased mortality of infected bees could be due to starvation imposed by N. ceranae development as well as direct damage to the infected enterocytes (Mayack and Naug, 2009). It is also conceivable that the degeneration of epithelial ventricular cells and subsequent reduction of longevity could be linked to oxidative stress triggered by N. ceranae infection (Vidau et al, 2014;Paris et al, 2017). Taken together these factors may cause a potential lethal outcome if the epithelium is not capable of replacing the damaged cells as previously shown for the Drosophila gut (Buchon et al, 2010).…”
Section: Resultsmentioning
confidence: 95%
“…This could therefore lead to the ISC renewal impairment we observed in our experiment using BrdU labelling, contrary to the work of Martín- To conclude, we have shown that N. ceranae can negatively alter the gut epithelium renewal rate and disrupt some signaling pathways involved in gut homeostasis. Considering the oxidative burst (Paris et al, 2017) and the higher energetic demand induced by infection (Vidau et al, 2014), alteration of gut renewal could be an another cause of the reduced longevity observed in infected honeybees, as the N. ceranae-induced damage does not appear to be compensated by the…”
Section: Resultsmentioning
confidence: 99%
“…The expression of AMPs may also be influenced, although results are ambiguous, and data on AMP-levels in the hemolymph are largely lacking [4,168] Second, pollutants may interfere either with detoxification mechanisms within the insect's body or the ability of social insects to sterilize stored food sources [169][170][171]. An increase in the production of ROS in the midgut after the oral uptake of insecticides can lead to oxidative stress and disruption of the oxidative balance in the gut [172], which may weaken the midgut's barrier function towards pathogens. The fungicide iprodione, but also heavy metals, have been shown to damage the midgut epithelium, which may, on one hand, result in a decrease immunocompetence of the tissue, and on the other, in a decrease in metabolic activity and decreased energetic efficiency due to mitochondrial damage [80,173].…”
Section: Pollutants and Disease Susceptibility Of Social Insects-mechmentioning
confidence: 99%